IMPROVING SUBSIDIZED FERTILIZER DISTRIBUTION PLANNING ACCURACY USING TIME SERIES FORECASTING AT PT PUPUK KUJANG CIKAMPEK - Harianto, Freddy
PT Pupuk Kujang is a subsidiary of PT Pupuk Indonesia. PT Pupuk Kujang has 2 urea plants, namely K1A and K1B plants, each year producing relatively stable amounts of urea fertilizer in the range of 990,000 tons. This production is divided to meet the needs of subsidized fertilizers, non-subsidized fertilizers, and as raw material for other fertilizers.